2019
DOI: 10.1177/1557988319834378
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Socioeconomic Status on the Presence and Degree of Erectile Dysfunction in Men With Coronary Artery Disease—A Cross-Sectional Study

Abstract: Impairment of social functioning and low economic status may lead to the development of cardiovascular disease (CVD). This study aimed to evaluate the relationship between socioeconomic status (SES) and erectile dysfunction (ED) in patients with clinically significant CVD. A total of 808 male patients with ischemic heart disease (IHD) were recruited. Socioeconomic and demographic data as well as occupational data and the presence of modifiable risk factors were collected. Erection quality was assessed using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Our regression models showed an influence of socioeconomic covariates on the BDI and FSFI scores. The strong impact of socioeconomic status on sexual functioning was also reported by other researchers [36], while age differences do not seem to be clinically significant (Appendix A Figure A1). In addition, naturally, there were differences in terms of COVID-19 contact characteristics because more people were infected or had more infected friends and relatives.…”
Section: Discussionsupporting
confidence: 77%
“…Our regression models showed an influence of socioeconomic covariates on the BDI and FSFI scores. The strong impact of socioeconomic status on sexual functioning was also reported by other researchers [36], while age differences do not seem to be clinically significant (Appendix A Figure A1). In addition, naturally, there were differences in terms of COVID-19 contact characteristics because more people were infected or had more infected friends and relatives.…”
Section: Discussionsupporting
confidence: 77%
“…A great percentage of uremic women complain of decrease in libido and pain during intercourse [ 31 ]. Azevedo et al claimed that the women with impaired sexual function had lower serum creatinine and phosphate level that can show association with nutritional status [ 32 ]. Guan et al reported that the main risk factors for decreased libido and lack of orgasm in CKD female patients are anemia, depression, and using beta-blockers [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated that the increased calcium level is associated with sexual dysfunction in male undergoing PD referring to the vascular etiology of erectile impairment [ 32 ]. The reproductive hormonal disturbance is the other reason for erectile dysfunction [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, poorer sexual function among socially disadvantaged men. A possible explanation is that lower SES is associated with higher risk of cardiovascular disease 38 and less participation in physical activity, 39 both of which can lead to poorer sexual function. Another interesting finding was improved sexual functioning among men starting AS in more recent years.…”
Section: Discussionmentioning
confidence: 99%